Developing Digital English-Speaking Materials for Students at Islamic Senior High School - Widyastuti, Friska; Santaria, Rustan; Sukirman, Sukirman (Register Journal, 2025)
Limited learning is the critical gap in English-speaking materials for Islamic senior high schools in Indonesia, which is that students must struggle, including a lack of vocabulary, grammatical errors, pronunciation difficulties, and poor fluency. Although current research has focused on all educational levels, there remains a notable scarcity of materials integrating Islamic values within communicative English teaching frameworks. The research aims to develop digital English-speaking materials that embed Islamic values into pedagogically sound language learning activities while emphasizing authentic communicative competence as the primary objective. The research employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model through a Research and Development approach. Data were collected through needs analysis, expert validation, classroom observations, and student questionnaires at MA Al-Falah Lemahabang. The developed e-book encompasses seven fundamental public speaking aspects integrated with Quranic verses and Islamic themes, including the Five Pillars of Islam, Ramadhan, charity, halal food ethics, and Islamic greetings. Based on the results of the research that thematic coherence between Islamic content and communicative tasks expands language learning by providing authentic contexts for giving opinions, describing, and narrating. Expert validation confirms that moral elements complement rather than overshadow language-learning goals. However, critical limitations include predominantly text-based digitization rather than truly interactive multimodal resources, single-site implementation restricting generalizability, and tensions between religious contextualization and activities requiring critical analysis or disagreement. The materials successfully balance linguistic objectives with value-based outcomes, contributing to improved speaking competence, cultural sensitivity, and critical intercultural competence. Future development should incorporate multimedia elements, interactive simulations, explicit integration of critical discourse skills, multi-site implementations, and longitudinal studies to ensure Islamic content enhances rather than constrains authentic language use.